Rapid endothelial cytoskeletal reorganization enables early blood–brain barrier disruption and long-term ischaemic reperfusion brain injury - Yejie Shi (Nature Portfolio, 2016)
Matrix metalloproteinases (MMPs) released from infiltrating immune cells are a major contributor to blood-brain barrier (BBB) breakdown following stroke. Here, the authors identify an early, MMP-independent BBB breakdown mechanism caused by rapid cytoskeletal rearrangements in endothelial cells, which could be inhibited by ADF.